The integration of creative drama into science teaching - Arieli, Bracha (Bari) (Kansas State University, 2007)
This study explored the inclusion of creative drama into science teaching as an instructional strategy for enhancing elementary school students' understanding of scientific concepts. A treatment group of sixth grade students was taught a Full Option Science System (FOSS) science unit on Mixtures and Solutions with the addition of creative drama while a control group was taught using only the FOSS teaching protocol. Quantitative and qualitative data analyses demonstrated that students who studied science through creative drama exhibited a greater understanding of scientific content of the lessons and preferred learning science through creative drama. Treatment group students stated that they enjoyed participating in the activities with their friends and that the creative drama helped them to better understand abstract scientific concepts. Teachers involved with the creative drama activities were positively impressed and believed creative drama is a good tool for teaching science. Observations revealed that creative drama created a positive classroom environment, improved social interactions and self-esteem, that all students enjoyed creative drama, and that teachers' teaching style affected students' use of creative drama. The researcher concluded that the inclusion of creative drama with the FOSS unit enhanced students' scientific knowledge and understanding beyond that of the FOSS unit alone, that both teachers and students reacted positively to creative drama in science and that creative drama requires more time.
Keywords: creative drama; science teaching; Education, Elementary (0524); Education, Sciences (0714)